Genotype–phenotype correlations in individuals with pathogenic RERE variants. Issue 5 (25th January 2018) - Jordan, Valerie K.; Fregeau, Brieana; Ge, Xiaoyan; Giordano, Jessica; Wapner, Ronald J.; Balci, Tugce B.; Carter, Melissa T.; Bernat, John A.; Moccia, Amanda N.; Srivastava, Anshika; Martin, Donna M.; Bielas, Stephanie L.; et al.
Abstract: Heterozygous variants in the arginine‐glutamic acid dipeptide repeats gene ( RERE ) have been shown to cause neurodevelopmental disorder with or without anomalies of the brain, eye, or heart (NEDBEH). Here, we report nine individuals with NEDBEH who carry partial deletions or deleterious sequence variants in RERE . These variants were found to be de novo in all cases in which parental samples were available. An analysis of data from individuals with NEDBEH suggests that point mutations affecting the Atrophin‐1 domain of RERE are associated with an increased risk of structural eye defects, congenital heart defects, renal anomalies, and sensorineural hearing loss when compared with loss‐of‐function variants that are likely to lead to haploinsufficiency. A high percentage of RERE pathogenic variants affect a histidine‐rich region in the Atrophin‐1 domain. We have also identified a recurrent two‐amino‐acid duplication in this region that is associated with the development of a CHARGE syndrome‐like phenotype. We conclude that mutations affecting RERE result in a spectrum of clinical phenotypes. Genotype–phenotype correlations exist and can be used to guide medical decision making. Consideration should also be given to screening for RERE variants in individuals who fulfill diagnostic criteria for CHARGE syndrome but do not carry pathogenic variants in CHD7 . Abstract : We describe nine unrelated individuals who carry partial deletions or putatively deleterious sequence variants in RERE . An analysis of clinical and molecular data from individuals with mutations affecting RERE suggests the existence of novel genotype‐phenotype correlations and demonstrates that a high percentage of RERE pathogenic variants affect a histidine‐rich region in the Atrophin‐1 domain. We have also identified a recurrent two‐amino‐acid duplication in this region that is associated with the development of a CHARGE syndrome‐like phenotype.